Rectal amputations and resections for cancer: Round Table XXVII Uruguayan Congress Surgery: coordinator Carlos Gómez Fossati - Gómez Fossati, Carlos; Bergalli, Luis; Crestanello, Francisco; Harretche, Martín; Kamaid, Emil (Cirugía del Uruguay, 1977)
Resecti-ons and amputations of 'the rectum for cancer Technical aspects of resections and amputations of the rectum and rectosigmoid for cancer are analized. Consideration was given to various technical aspects, their application, basis and justification.